107. Intraoperative neurophysiologic monitoring in 145 surgical treatments for scoliosis. Issue 4 (April 2016) - Borio, A.; Milani, D.; Marmolino, S.; Mogno, M.; Serpella, D.; Costa, P.; Thiery, A.
Abstract : Post-operative sensory-motor outcome is related to intraoperative surgical or vascular complications. Intraoperative Neurophysiologic Monitoring (IONM) identifies changes to allow quick correction of the causes before neurological damages. The aim of the study is to assess the significance of IONM during scoliosis surgery, in particular for evaluating the relevance of motor evoked potential. 145 patients in TIVA/TCI anaesthesia were monitored through motor evoked potentials derived by upper and lower limbs' muscles (mMEPs) and Somatosensory Evoked Potentials derived from Erb-point and scalp by Median and Posterior Tibial nerve stimulation (SEPs). 94, 5% of patients were recordable, while 5, 5% presented no basal mMEPs and/or SEPs for previous pathologies and were non-elected. 2% had abortion of mMEPs for anaesthetic plane. 5, 5% presented fleeting alteration of peripheral responses from Erb-point during surgery. 6% suffered of transitory modification of neurophysiological parameters: 100% of the alterations hit the mMEPs and just 22, 2% the SEPs but anyone had only SEPs modifications in preserved mMEPs. Intraoperative combined SEPs and mMEPs monitoring is a safe, reliable and sensitive method to detect and reduce intraoperative injury to the spinal cord during scoliosis surgery, in particular, mMEPs are elective for early intraoperative detection of anterior medullar ischemia.